Public finance, aid, and post-conflict recovery - James K. Boyce (University of Massachusetts, Department of Economics, 2007)
In the wake of violent conflict, a key element of building a durable peace is building a state with the ability to collect and manage public resources. To implement peace accords and provide public services, the government must be able to collect revenue, allocate resources, and manage expenditure in a manner that is regarded by its citizens as effective and equitable. This paper addresses eight key issues related to this challenge. The first four pertain to resource mobilization: (i) How should distributional impacts enter into revenue policies? (ii) How can postwar external assistance do more to prime the pump of domestic revenue capacity? (iii) Should macroeconomic strictures prescribed for economic stabilization be relaxed to foster political stabilization? (iv) How should the benefits of external resources be weighed against their costs? The second four issues relate to the expenditure side of public finance: (i) How should the dynamics of conflict be factored into public spending policies? (ii) Can the pathologies of a 'dual public sector' one funded and managed by the government, the other by the aid donors be surmounted by channeling external resources through the government, with dual-control oversight mechanisms to reduce corruption? (iii) How should long-term fiscal sustainability enter into short-term expenditure decisions? (iv) Lastly, is there scope for more innovative solutions to postwar legacies of external debts?
Keywords: E61; E62; E63; F35; F51; F53; H20; H22; H50; 330; peacebuilding; revenue mobilization; external assistance; foreign aid; post-conflict transitions; public expenditure; horizontal equity; odious debt